2016
DOI: 10.1371/journal.pone.0161171
|View full text |Cite
|
Sign up to set email alerts
|

Home-Based and Facility-Based Directly Observed Therapy of Tuberculosis Treatment under Programmatic Conditions in Urban Tanzania

Abstract: IntroductionDecentralization of Directly Observed Treatment (DOT) for tuberculosis (TB) to the community (home-based DOT) has improved the coverage of TB treatment and reduced the burden to the health care facilities (facility-based DOT). We aimed to compare TB treatment outcomes in home-based and facility-based DOT under programmatic conditions in an urban setting with a high TB burden.MethodologyA retrospective analysis of a cohort of adult TB patients (≥15 years) routinely notified between 2010 and 2013 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 27 publications
3
16
0
1
Order By: Relevance
“…With approximately 4.4 million people, Dar es Salaam is a TB hotspot region in Tanzania notifying 22% of all TB cases in Tanzania [ 17 ]. The details of the study setting have been described previously [ 18 22 ]. Participants included as TB cases were sputum smear-positive adult TB patients (>18 years), while those included as controls were exposed household contacts who did not have active TB.…”
Section: Methodsmentioning
confidence: 99%
“…With approximately 4.4 million people, Dar es Salaam is a TB hotspot region in Tanzania notifying 22% of all TB cases in Tanzania [ 17 ]. The details of the study setting have been described previously [ 18 22 ]. Participants included as TB cases were sputum smear-positive adult TB patients (>18 years), while those included as controls were exposed household contacts who did not have active TB.…”
Section: Methodsmentioning
confidence: 99%
“…The overall HIV prevalence in the general adult population in Dar es Salaam is 5.2% [ 19 ]. The study area includes two TB sub-districts, Wailes I and Wailes II, whose patients are clinically managed at the Temeke district hospital and the two associated TB diagnostic and treatment centers of Tambukareli and Pasada [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…This finding is also supported by the experience of Belarus and Australia -demonstrating effectiveness of video-observed treatment [38,39]. There are also some controversies about the consequences of the home-based treatment in the literature [40,41]. While some authors found that home-based treatment was safe and acceptable for both the patients and health care providers, others indicate that treating patient at home may lead to uncontrolled and missed adverse events [40,41].…”
Section: Articlementioning
confidence: 78%